1953
DOI: 10.1542/peds.12.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Electrolyte Composition of Sweat in Cystic Fibrosis of the Pancreas

Abstract: The electrolyte composition of sweat secreted in response to a standard mild thermal stimulus was found to be abnormal in 43 patients with cystic fibrosis of the pancreas. Sodium and chloride concentrations in sweat were 2 to 4 times as high as those found in 50 patients with a variety of other diseases. Sweat potassium levels were also increased in cystic fibrosis of the pancreas although not to the same extent. In contrast, the amount of sweat was not significantly different in patients with fibrocystic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2
2

Year Published

1961
1961
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(31 citation statements)
references
References 0 publications
0
27
2
2
Order By: Relevance
“…In addition, the father in Family B experienced multiple episodes of dehydration, volume depletion, and vomiting, very similar to the cases of heat prostration reported in children with CF during a summer heat wave in 1948 ( 25 ). As shown later, loss of salt from the sweat glands caused volume depletion and abnormally low serum sodium, chloride, and potassium in the children with CF ( 26 ), and we presume the same mechanism was responsible for the electrolyte abnormality episodes in the father of Family B. Of note are reports of 3 children who presented with dehydration and/or hypochloremic metabolic alkalosis (salt-loss syndrome) and were thereafter identified to have F312del (reported as ΔF311 or DF311) and other severe CF-causing variants ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the father in Family B experienced multiple episodes of dehydration, volume depletion, and vomiting, very similar to the cases of heat prostration reported in children with CF during a summer heat wave in 1948 ( 25 ). As shown later, loss of salt from the sweat glands caused volume depletion and abnormally low serum sodium, chloride, and potassium in the children with CF ( 26 ), and we presume the same mechanism was responsible for the electrolyte abnormality episodes in the father of Family B. Of note are reports of 3 children who presented with dehydration and/or hypochloremic metabolic alkalosis (salt-loss syndrome) and were thereafter identified to have F312del (reported as ΔF311 or DF311) and other severe CF-causing variants ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 83%
“…Following benchtop characterization in buffer solutions, we demonstrate that the printed electrode-based sensors are equally high performing in biofluids including sweat, urine, and saliva. Na + is chosen as the target analyte as its concentration in these biofluids is relevant to assessing kidney disease and heart failure among other health complications, as well as for monitoring electrolyte loss or dehydration during exercise. , Na + sensors are fabricated on the printed electrode arrays and characterized using multipoint calibration to determine their concentration-to-potential curve. This information is used to accurately covert the sensor signal to a concentration measurement for the sweat, urine, and saliva samples.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Vairo et al (2017) showed that electrolyte concentration in sweat sampled following physical activity did not reflect concentrations in plasma. 70 This is not to underestimate sweat's utilityfor example, electrolyte composition of sweat is known to be abnormal in cystic fibrosissodium and chloride concentrations are much higher 71,72 and sweat chloride concentration is a common diagnostic tool for cystic fibrosis. 73 In health, electrolytes such as sodium and potassium could be related to hydration status, and characterization of sweat electrolytes of athletes could suggest modifications of diet and training habits.…”
Section: Sensors and Diagnosticsmentioning
confidence: 99%